Theoretical Analysis of Rockfall Impacts on the Soil Cushion Layer of Protective Structures - Xing Wang; Yongxu Xia; Tianyue Zhou (Advances in Civil Engineering)
During the Wenchuan Earthquake, with a magnitude of 5.12, collapses and rockfall hazards persisted for a long time after the initial investigations carried out by research fellow S. M. He and his team at the scene of the disaster in October 2008. It is possible that additional incidents of rockfalls in large quantities may continue in the same areas over the next ten to fifteen years. Furthermore, in the vast mountainous region of western China, the topographic relief is evident, and earthquakes occur frequently. Therefore, it is difficult to effectively defend against rockfall hazards. When designing protective structures, the key issue is the analysis of the mechanical response mechanism of the soil cushion layer of the upper cushion when subjected to the impact of rockfall. As such, a theoretical method was used to perform such an analysis. The cavity expansion and energy conservation model were adopted. Analytical solutions for the impact force and penetration depth were then derived. Furthermore, the impact force and penetration depth of rockfall were studied with the LS-DYNA software to obtain values for the impact forces and the penetration depth. Finally, the reliability of the theoretical method was evaluated using the cavity expansion, energy conservation, numerical simulation, Hertz, Japanese, Swiss, Australian, B. S. Guan, tunnel manual, and subgrade methods based on an engineering model. The results show that the cavity expansion and the energy conservation methods yielded consistent results. Meanwhile, the cavity expansion and the energy conservation methods also yielded consistent results with the numerical simulation, Japanese (obtained by laboratory experiment), Swiss (obtained by laboratory experiment), and Australian (obtained by field experiment) methods. The relevant methods and conclusions shall therefore be applied to the design of rockfall protection structure in future investigations.